Respuesta :
[tex]S_n=1\cdot1!+2\cdot2!+\cdots+n\cdot n![/tex]
[tex]S_n=(1+1-1)\cdot1!+(2+1-1)\cdot2!+\cdots+(n+1-1)\cdot n![/tex]
[tex]S_n=(2\cdot1!-1\cdot1!)+(3\cdot2!-1\cdot2!)+\cdots+\bigg((n+1)n!-\cdot n!\bigg)[/tex]
[tex]S_n=(2!-1!)+(3!-2!)+\cdots+\bigg((n+1)!-1\cdot n!\bigg)[/tex]
[tex]S_n=-1!+(n+1)![/tex]
[tex]S_n=(n+1)!-1[/tex]
[tex]S_n=(1+1-1)\cdot1!+(2+1-1)\cdot2!+\cdots+(n+1-1)\cdot n![/tex]
[tex]S_n=(2\cdot1!-1\cdot1!)+(3\cdot2!-1\cdot2!)+\cdots+\bigg((n+1)n!-\cdot n!\bigg)[/tex]
[tex]S_n=(2!-1!)+(3!-2!)+\cdots+\bigg((n+1)!-1\cdot n!\bigg)[/tex]
[tex]S_n=-1!+(n+1)![/tex]
[tex]S_n=(n+1)!-1[/tex]
The closed form of the equation is: [tex]$S_n = (n + 1)! -1[/tex]
The equation is given as:
[tex]$S_n = 1 \cdot 1! + 2 \cdot 2! + \ldots + n \cdot n!.$[/tex]
Rewrite the equation as:
[tex]$S_n = (1) \cdot 1! + (2) \cdot 2! + \ldots + (n) \cdot n!.$[/tex]
Add 0 to the expressions in bracket
[tex]$S_n = (1 + 0) \cdot 1! + (2 + 0) \cdot 2! + \ldots + (n + 0) \cdot n!.$[/tex]
Express 0 as 1 - 1
[tex]$S_n = (1 + 1 - 1) \cdot 1! + (2 + 1 - 1) \cdot 2! + \ldots + (n + 1 - 1) \cdot n!.$[/tex]
Evaluate the sums
[tex]$S_n = (2 - 1) \cdot 1! + (3 - 1) \cdot 2! + \ldots + (n + 1 - 1) \cdot n!.$[/tex]
Open the brackets
[tex]$S_n = 2 \cdot 1!- 1 \cdot 1! + 3 \cdot 2!- 1 \cdot 2! + \ldots + (n + 1 ) \cdot n!- 1 \cdot n!.$[/tex]
Simplify
[tex]$S_n = (2!- 1!) + (3!- 2!) + \ldots +[ (n + 1 )!- 1 \cdot n!.$][/tex]
Rewrite the above equation in terms of n
[tex]$S_n = (n + 1)! -1![/tex]
Evaluate 1!
[tex]$S_n = (n + 1)! -1[/tex]
Hence, the closed form of the equation is:
[tex]$S_n = (n + 1)! -1[/tex]
Read more about factorials at:
https://brainly.com/question/8119212